Comparison of vaginal examination methods to evaluate urovagina and purulent vaginal discharge in periestrous dairy cows - Dai ISHIYAMA; Fumie MAGATA; Fuko MATSUDA (The Journal of Reproduction and Development)
Urovagina and purulent vaginal discharge (PVD) are usually diagnosed using a speculum, Metricheck device, or gloved hand. In periestrous dairy cows, a comparative study of these vaginal examinations for diagnosing urovagina or PVD has not yet been conducted. This study aimed to identify an effective vaginal examination method for periestrous dairy cows to ensure successful artificial insemination. Data were collected from 227 Holstein-Friesian cows during 300 occurrences of spontaneous estrus. Urovagina was evaluated using the speculum and gloved-hand methods and classified as mild, moderate, or severe. Vaginal discharge was evaluated using speculum, Metricheck, and gloved-hand methods and classified as vaginal discharge score (VDS) 0–5, with 2–5 defined as PVD-positive. Sensitivity and specificity of the gloved-hand versus speculum method in diagnosing urovagina, speculum versus Metricheck method, and gloved-hand versus Metricheck method in diagnosing PVD positivity were equivalent. The incidence of urovagina tended to be higher with the gloved-hand than with the speculum method. The incidence of PVD positivity tended to be higher with the gloved-hand than with the speculum and Metricheck methods. To analyze the correlation between pregnancy outcomes and mucus characteristics diagnosed using each method, logistic regression analysis was conducted, and the final models were compared. In this model, urovagina was selected as the explanatory variable and was associated with poor pregnancy. The results indicate that the gloved-hand method would be useful for managing fertility by detecting urovagina and PVD in periestrous dairy cows.